2010
DOI: 10.1155/2010/939171
|View full text |Cite
|
Sign up to set email alerts
|

Global Modeling of the Oceanic Source of Organic Aerosols

Abstract: The global marine organic aerosol budget is investigated by a 3-dimensional chemistry-transport model considering recently proposed parameterisations of the primary marine organic aerosol (POA) and secondary organic aerosol (SOA) formation from the oxidation of marine volatile organic compounds. MODIS and SeaWiFS satellite data of Chlorophyll-a and ECMWF solar incoming radiation, wind speed, and temperature are driving the oceanic emissions in the model. Based on the adopted parameterisations, the SOA and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 76 publications
5
126
1
2
Order By: Relevance
“…Although high phytoplankton activity in the surface ocean can emit a certain amount of isoprene and other BVOCs, their levels are rather minor compared to emissions from terrestrial plants. 9,10,53 Here, the NAQPMS model results demonstrated that at Mumbai, SOA loadings were lower in June 2006 (about 0.6 μg m −3 ) than those in February 2007 (1.5 μg m −3 ). The GEOS-Chem model results again showed that SOA loadings were much lower (about 0.072 μg m −3 ) in summer than those (0.51 μg m −3 ) in winter.…”
Section: ■ Materials and Methodsmentioning
confidence: 68%
“…Although high phytoplankton activity in the surface ocean can emit a certain amount of isoprene and other BVOCs, their levels are rather minor compared to emissions from terrestrial plants. 9,10,53 Here, the NAQPMS model results demonstrated that at Mumbai, SOA loadings were lower in June 2006 (about 0.6 μg m −3 ) than those in February 2007 (1.5 μg m −3 ). The GEOS-Chem model results again showed that SOA loadings were much lower (about 0.072 μg m −3 ) in summer than those (0.51 μg m −3 ) in winter.…”
Section: ■ Materials and Methodsmentioning
confidence: 68%
“…The emission of alkyl nitrates from the ocean has been linked to both the concentration of chlorophyll and sea temperature (Chuck et al, 2002;Dahl and Saltzman, 2008). A strong seasonality exists in the chlorophyll concentrations in the SH (Myriokefalitakis et al, 2010) resulting in maximal concentrations occurring during the boreal wintertime; therefore any resulting emission flux is likely to exhibit a similar seasonality. The small emission of CH 3 ONO 2 measured from biomass and savannah fires (∼ 18 Gg yr −1 , Simpson et al, 2002) is an order of magnitude lower than the ocean emission flux and thus is not included.…”
Section: Definition Of the Emission Scenarios And Sensitivity Studiesmentioning
confidence: 99%
“…As we do not apply either a diurnal or seasonal variation in the emission term, the model cannot be expected to be able to capture exactly the same profile. To improve on this, future studies could exploit chlorophyll maps from satellites such as MODIS as demonstrated by Myriokefalitakis et al (2010) for marine organic aerosol formation. However, our study is more focussed on the influence of the chemical production term therefore we consider developing such an approach to be beyond the scope of this present study.…”
Section: Comparisons Against Surface and Aircraft Measurementsmentioning
confidence: 99%
“…Recent estimates of OM from marine sources range between 2.3 to 75 TgC yr −1 Roelofs, 2008;Gantt et al, 2009;Ito and Kawamiya, 2010;Myriokefalitakis et al, 2010;Long et al, 2011;Vignati et al, 2010). This wide range reflects challenges and large uncertainties associated with quantifying these emissions, as well as differences in treatment (including both sub-micron and super-micron size ranges or primary and secondary sources).…”
Section: K Lapina Et Al: Marine Aerosol Backgroundmentioning
confidence: 99%